2014
DOI: 10.1152/ajpheart.00048.2014
|View full text |Cite
|
Sign up to set email alerts
|

A novel adipocytokine, omentin, inhibits platelet-derived growth factor-BB-induced vascular smooth muscle cell migration through antioxidative mechanism

Abstract: Kazama K, Okada M, Yamawaki H. A novel adipocytokine, omentin, inhibits platelet-derived growth factor-BB-induced vascular smooth muscle cell migration through antioxidative mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Omentin suppresses growth of vascular smooth muscle cells through an AMPK-dependent mechanism. Omentin also inhibits growth factor-induced smooth muscle cell migration through the anti-oxidative mechanism 79) . More recently, we have shown that omentin attenuates atherosclerotic lesion formation in a mouse model of atherosclerosis 80) .…”
Section: Resultsmentioning
confidence: 99%
“…Omentin suppresses growth of vascular smooth muscle cells through an AMPK-dependent mechanism. Omentin also inhibits growth factor-induced smooth muscle cell migration through the anti-oxidative mechanism 79) . More recently, we have shown that omentin attenuates atherosclerotic lesion formation in a mouse model of atherosclerosis 80) .…”
Section: Resultsmentioning
confidence: 99%
“…In vSMC, omentin inhibits TNF-ainduced expression of vascular cell adhesion molecule 1 and platelet-derived growth factor BB-induced migration through antioxidant mechanism. 19,20 Thus, omentin is an anti-inflammatory adipokine with a potent vasodilatory effect.…”
Section: Introductionmentioning
confidence: 99%
“…Serum omentin-1 concentrations were markedly reduced in patients with type 2 diabetes [7]. Omentin inhibited platelet-derived growth factor BB-induced vascular smooth muscle cell migration by reducing oxidative stress [18]. This indicates that omentin-1 may serve as a target for treating hypertension by inhibiting vascular structural remodeling [18].…”
Section: Discussionmentioning
confidence: 99%
“…Omentin inhibited platelet-derived growth factor BB-induced vascular smooth muscle cell migration by reducing oxidative stress [18]. This indicates that omentin-1 may serve as a target for treating hypertension by inhibiting vascular structural remodeling [18]. In addition, omentin treatment inhibited pulmonary arterial hypertension in rats by inhibiting vascular structural remodeling and abnormal contractile reactivity [6].…”
Section: Discussionmentioning
confidence: 99%